Occupational health in a hospital setting - Dorothy Blacklaws (AOSIS, 1981)
Health services and especially hospitals, are amongst the employers with the largest number of employees in the country. Those employed in the service have the right to as high a standard of occupational health as found in industry at its best. Health services in hospitals should use techniques of preventive employees and reduces absenteeism due to sickness and other causes. It health requirements of the employees. Hospitals should serve as examples to the public regarding health education, preventive medicine and job safety. Hospitals have a moral and legal obligation to: - provide a safe and healthful working environment for employees; - protect employees from special risks and hazards associated with their occ u p a t i o n s , su c h as c o n t a g io u s diseases; - protect patients from risks associated with unhealthy employees. Experience in other employee groups has shown that an occupational health service results in healthier, more effective employees and reduces absenteeism due to sickness and other causes. It also reduces labour turnover and Workmen's compensation and other insurance claims.